Characterizing the performance of a do-it-yourself (DIY) box fan air filter. Issue 6 (21st April 2022) - Dal Porto, Rachael; Kunz, Monet N.; Pistochini, Theresa; Corsi, Richard L.; Cappa, Christopher D.
Abstract: Air filtration serves to reduce concentrations of particles in indoor environments. Most standalone, also referred to as portable or in-room, air filtration systems use HEPA filters, and cost generally scales with the clean air delivery rate. A "do-it-yourself" lower-cost alternative, known as the Corsi-Rosenthal Box, that uses MERV-13 filters coupled with a box fan has been recently proposed, but lacks systematic performance characterization. We have characterized the performance of a five-panel Corsi-Rosenthal air cleaner using both research-grade instrumentation (an aerodynamic particle sizer, APS) and a low-cost particle sensor. Measurements of size-resolved and overall decay rates of aerosol particles larger than 0.5 microns emitted into rooms of varying size with and without the air cleaner allowed for determination of the apparent clean air delivery rate—both as a function of size and integrated across particle sizes for a number-weighted median particle diameter of 1.2 ± 0.12 microns. The measurements made in the different rooms produced similar results, demonstrating the robustness of the method used. The size-integrated effective clean air delivery rate increases with fan speed, from about 600 to 850 ft 3 min −1 (1019 to 1444 m 3 h −1 ) as determined with the APS. The low-cost sensor yields similar clean air delivery rates as the APS, demonstrating a method by which others who lack access to research-grade instruments can determine the effectiveness of Corsi-Rosenthal Boxes that use components that differ from those used here. Overall, our results demonstrate that our Corsi-Rosenthal air cleaner efficiently reduces suspended particle concentrations in indoor environments.